Analisis Kemampuan Berpikir Kreatif Matematis Siswa pada Materi Peluang Kelas XI IPA I SMAN 1 Bangun Purba - Yulia Citra; Ratri Isharyadi; Hera Deswita (Jurnal Pendidik Indonesia, 2022)
Mathematical creative thinking is the ability to think that aims to create or find new, different, unusual, and original ideas that bring definite and precise results. This study aims to determine the mathematical creative thinking skills of students of SMAN 1 Bangun Purba class XI IPA 1. This research was conducted on 23 students in class XI IPA 1 using descriptive qualitative methods. The instrument used was a mathematical creative thinking ability test which consisted of 4 items on students’ mathematical creative thinking abilities on the probability material accompanied by interviews with students. Indicators of mathematical creative thinking abilities used are fluency, flexibility, originality and elaboration. This study concludes that the mathematical creative thinking ability of students of SMAN 1 Bangun Purba class XI IPA 1 has an average of 72.3 in the high category. At the same time, the presentation for fluency indicators is 74%, flexibility indicators 72%, originality indicators 66%, and indicators. Elaboration 77%. The highest percentage of creative thinking ability characteristics is elaboration, and the lowest is originality.